Low Protective Efficacy of the Current Japanese Encephalitis Vaccine against the Emerging Genotype 5 Japanese Encephalitis Virus - Cao, Lei; Fu, Shihong; Gao, Xiaoyan; Li, Minghua; Cui, Shiheng; Li, Xiaolong; Cao, Yuxi; Lei, Wenwen; Lu, Zhi; He, Ying; Wang, Huanyu; Yan, Jinghua; et al. (PLoS neglected tropical diseases, 2016)
The current Japanese encephalitis (JE) vaccine derived from G3 JE virus (JEV) can induce protective immunity against G1-G4 JEV genotypes. However, protective efficacy against the emerging G5 genotype has not been reported. Using in vitro and in vivo tests, biological phenotype and cross-immunoreactions were compared between G3 JEV and G5 JEV (wild strains). The PRNT90 method was used to detect neutralizing antibodies against different genotypes of JEV in JE vaccine-immunized subjects and JE patients. In JE vaccine-immunized mice, the lethal challenge protection rates against G3 and G5 JEV wild strains were 100% and 50%, respectively. The seroconversion rates (SCRs) of virus antibodies against G3 and G5 JEV among vaccinated healthy subjects were 100% and 35%, respectively. All clinically identified JE patients showed high levels of G3 JEV neutralizing antibodies (≥1:10-1280) with positive serum geometric mean titers (GMTs) of 43.2, while for G5 JEV, neutralizing antibody conversion rates were only 64% with positive serum GMTs of 11.14. Moreover, the positive rate of JEV neutralizing antibodies against G5 JEV in pediatric patients was lower than in adults. Low levels of neutralizing/protective antibodies induced by the current JE vaccine, based on the G3 genotype, were observed against the emerging G5 JEV genotype. Our results demonstrate the need for more detailed studies to reevaluate whether or not the apparent emergence of G5 JEV can be attributed to failure of the current vaccine to induce appropriate immune protectivity against this genotype of JEV.